Searches and seizures of electronic devices in european criminal proceedings:a new pattern for independent review? - Bernardini, Lorenzo; Sanvitale , Francesco (Revista Ítalo-española de Derecho procesal, 2023)
In the field of digital searches and seizures, there is not a comprehensive EU regulation. Accordingly, the Authors analyze the scope and the content of Article 8 ECHR in order to depict the minimum standards stemming thereof for what concerns the need for both a prior and an ex post facto independent oversight. Against this background, the Italian legal framework will serve as a benchmark in order to find to what extent the aforementioned guarantees are safeguarded, and which impact could the relevant ECtHR’s case-law have at the domestic level.